Embryonic Stem Cell Research Ethical and Legal Controversies - Patil , Amit M (Journal of Indian Academy of Forensic Medicine, 2014)
The discovery of stem cells particularly embryonic stem cells with its possible clinical application  has generated great curiosity amongst medical professionals and general public. Embryonic stem cell  research has become a challenging issue for biomedical scientists, policy makers and regulatory bodies.  The key controversial issue is the determination of moral and legal status of the embryo as  embryo stem cell research involves retrieving embryonic tissue from spare embryos leading to their  destruction. This embryo that has the full capacity to develop into a human being is sacrificed for the  benefit of others. Global regulations monitoring stem cell research are also troubled with similar ethical  and moral issues associated with it. The main source of embryonic tissue is the spare or supernumerary  embryos created during infertility treatment by artificial reproductive techniques (ART). Sadly, in absence  of regulatory provisions to govern them, the field of ART is open for all forms of medical malpraxis bearing  direct implications on embryonic stem cell research. This article is an attempt to seek clarity on the  concept of embryonic stem cell research and contentious issues associated with it.
Keywords: Stem cells; embryonic stem cell research; Moral and legal status of embryo; ART; Global regulation